A Survey of Anxiety and Depressive Symptoms in Pulmonary Tuberculosis Patients With and Without Tracheobronchial Tuberculosis - Wang, Xiao-bo; Li, Xue-lian; Zhang, Qing; Zhang, Juan; Chen, Hong-yan; Xu, Wei-yuan; Fu, Ying-hui; Wang, Qiu-yue; Kang, Jian; Hou, Gang (Frontiers in Psychiatry, 2018)
Background and objective: Anxiety/depression and tuberculosis are global public health problems. The incidence of psychiatric morbidities is high among tuberculosis patients. However, little is known about the prevalence of anxiety and depression among Chinese pulmonary tuberculosis (PTB) patients, especially those with tracheobronchial tuberculosis (TBTB). The goal of the present study was to explore the prevalence of and associated factors of anxiety and depressive symptoms among PTB patients with and without TBTB. Methods: A cross-sectional survey of PTB patients from three hospitals in Liaoning, China, was conducted using a structured questionnaire. Depression and anxiety were evaluated by using the Hospital Anxiety and Depression Scale (HADS) and the Patient Health Questionnaire-9 (PHQ-9). Results: According to HADS and PHQ-9, 17.73% and 18.13% of 1252 PTB patients, respectively, had significant depressive symptoms and based on HADS scale, 18.37% had significant anxiety symptoms. Approximately 70% of patients with probable depression also had significant anxiety symptoms, and vice versa, and 69.6% patients with anxiety symptoms were also diagnosed with probable depression in our study population. Dyspnea and TBTB were significantly associated with depressive symptoms. Other depressive symptoms-related factors included age, divorce, abnormal body mass index (BMI), and low income. Patients with lower incomes, symptoms of dyspnea, or a combination of ≥3 clinical symptoms had an increased risk of anxiety symptoms, while patients with occasional or frequent alcohol consumption had a reduced risk of anxiety symptoms. Conclusion: Depressive and anxiety symptoms are common among PTB patients, especially those with TBTB. Screening for depression and anxiety is essential for identifying patients who require further psychosocial assessment and support.